Role of Livestock in Economic Development - Luitel, Chakrapani (Tribhuvan University Journal, 2010)
Not available. Key words: Livestock; Economic development; Nepal Tribhuvan University Journal Vol. XIX, 1996 Page: 121-129 Uploaded date: Dec. 10, 2010